2016
DOI: 10.4028/www.scientific.net/msf.858.283
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Variable Range Hopping in Heavy Al Implanted 4H-SiC

Abstract: In this work, we confirm and extend the results of a previous study where a variable range hopping transport through localized impurity states has been found to dominate the electrical transport properties of 3×1020 cm-3 and 5×1020 cm-3 Al+ implanted 4H-SiC layers after 1950-2000 °C post implantation annealing. In this study, samples with longer annealing times have been taken into account. The temperature dependence of these sample conductivity follows a variable range hopping law, consistent with a nearly tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…However, concerning the last point, it has been demonstrated by Energy Dispersive X-ray Spectroscopy (EDS) characterizations that C defects are not directly related to Al segregation or precipitation phenomena. 18,19 The observation that C defects are not Al-rich defects and, as above described, that their density peaks in an interface region between the Al rich plateau and the unimplanted substrate suggests that their presence may contribute to release the lattice strain present in the 4H-SiC doped surface layer. Other authors have shown that extra planes formed after the implantation and annealing process may be responsible for a c-lattice expansion observed in doped 4H-SiC epi-layers irrespective of the implanted ion species.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…However, concerning the last point, it has been demonstrated by Energy Dispersive X-ray Spectroscopy (EDS) characterizations that C defects are not directly related to Al segregation or precipitation phenomena. 18,19 The observation that C defects are not Al-rich defects and, as above described, that their density peaks in an interface region between the Al rich plateau and the unimplanted substrate suggests that their presence may contribute to release the lattice strain present in the 4H-SiC doped surface layer. Other authors have shown that extra planes formed after the implantation and annealing process may be responsible for a c-lattice expansion observed in doped 4H-SiC epi-layers irrespective of the implanted ion species.…”
Section: Resultsmentioning
confidence: 89%
“…2b, we can see that the strong anisotropic hole transport takes place in a surface layer confined by and containing stacking faults. These defects are probably at the origin of the strong anisotropy of the conductivity 19 that should be avoided when using the ion implantation technology for electronic device fabrication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although HREM thickness determinations may be affected by a systematic error due to delocalization effects (which are in fact present in the images), efforts have been made to reduce these effects. However they cannot be completely eliminated when using aberrated microscopes [26].…”
Section: Methodsmentioning
confidence: 99%
“…Details of these analyses will be given elsewhere [23][24][25][26] and only some brief notes are given here. Firstly, SE studies were carried out using a Woollam M2000DI spectroscopic ellipsometer at MFA, Budapest.…”
Section: Methodsmentioning
confidence: 99%